Functionalization of PCL-Based Fiber Scaffolds with Different Sources of Calcium and Phosphate and Odontogenic Potential on Human Dental Pulp Cells - Anselmi, Caroline [UNESP] (2024)
This study investigated the incorporation of sources of calcium, phosphate, or both into electrospun scaffolds and evaluated their bioactivity on human dental pulp cells (HDPCs). Additionally, scaffolds incorporated with calcium hydroxide (CH) were characterized for degradation, calcium release, and odontogenic differentiation by HDPCs. Polycaprolactone (PCL) was electrospun with or without 0.5% w/v of calcium hydroxide (PCL + CH), nano-hydroxyapatite (PCL + nHA), or β-glycerophosphate (PCL + βGP). SEM/EDS analysis confirmed fibrillar morphology and particle incorporation. HDPCs were cultured on the scaffolds to assess cell viability, adhesion, spreading, and mineralized matrix formation. PCL + CH was also evaluated for gene expression of odontogenic markers (RT-qPCR). Data were submitted to ANOVA and Student’s t-test (α = 5%). Added CH increased fiber diameter and interfibrillar spacing, whereas βGP decreased both. PCL + CH and PCL + nHA improved HDPC viability, adhesion, and proliferation. Mineralization was increased eightfold with PCL + CH. Scaffolds containing CH gradually degraded over six months, with calcium release within the first 140 days. CH incorporation upregulated DSPP and DMP1 expression after 7 and 14 days. In conclusion, CH- and nHA-laden PCL fiber scaffolds were cytocompatible and promoted HDPC adhesion, proliferation, and mineralized matrix deposition. PCL + CH scaffolds exhibit a slow degradation profile, providing sustained calcium release and stimulating HDPCs to upregulate odontogenesis marker genes.